2009
DOI: 10.1080/01140670909510261
|View full text |Cite
|
Sign up to set email alerts
|

Soil physical properties and infiltration after long‐term no‐tillage and ploughing on the Chinese Loess Plateau

Abstract: Water is the most limiting factor for crop production in dryland farming. A better understanding of the long-term impact of tillage and residue management systems on soil structure and water infiltration is necessary for the further development of conservation tillage practice to improve water use efficiency. The objectives of this study were to assess the influence of no-till with residue retention (NT) and conventional (plough) tillage with residue removal (CT) on soil properties and soil water transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 28 publications
8
32
0
1
Order By: Relevance
“…This is consistent with the findings of Mulumba et al [25], who stated that long-term residue incorporation has increasingly positive impacts on soil porosity. Previous studies also found that soil porosity increased by 5.5% at soil depths of 0-30 cm, with straw incorporation practices compared with traditional methods [26,27]. Additionally, Zhang et al [28] reported that straw incorporation increased the SOC concentration and reduced bulk density, thereby improving total porosity, aeration, and water-holding capacity.…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with the findings of Mulumba et al [25], who stated that long-term residue incorporation has increasingly positive impacts on soil porosity. Previous studies also found that soil porosity increased by 5.5% at soil depths of 0-30 cm, with straw incorporation practices compared with traditional methods [26,27]. Additionally, Zhang et al [28] reported that straw incorporation increased the SOC concentration and reduced bulk density, thereby improving total porosity, aeration, and water-holding capacity.…”
Section: Discussionmentioning
confidence: 92%
“…Soil quality is the capacity of a soil to function within ecosystem boundaries, sustain biological productivity, maintain environmental quality, and promote plant and animal health [8]. The beneficial effects of CA in terms of better soil quality are reflected through an improvement in soil organic carbon in the top 10 cm soil depth [7,31], enhanced water infiltration rate as indicated in Figure 2 [22,32], enhanced water holding capacity [11,22], lower bulk density [11,33], higher aggregates stability [7,33] and better soil structure [33]. For improved water infiltration and capture, SOM can be maintained by limiting soil aggregates and structure breakdown through tillage practices.…”
Section: The Effect Of Ca On Soil Qualitymentioning
confidence: 99%
“…The presence of crop residues over the soil surface prevents aggregate breakdown by direct raindrop impact as well as by rapid wetting and drying of soils. There are also reports showing slight or no differences in D b values between CT and ZT in the surface soil layers [58][59][60]. At 11-15-cm and 16-20-cm depths, D b was significantly higher in T1, T2, T3 and T4 than in ZT-DSR (T5 and T6).…”
Section: Soil Physical Parameters Soil Bulk Density (D B )mentioning
confidence: 89%
“…The higher rate of infiltration in ZT with residue retention treatment compared to TPR may not be desirable in rice when using flood irrigation because of high percolation losses of water. The solution to such a problem lies in the use of soil matric potential based irrigation approach and sub-surface drip irrigation method in RWS reported similar infiltration rates for CT and ZT plots, probably due to the similarity of soil physical properties in the upper layer [59,79]. However, when water infiltrated into deeper soil layers, ZT plots showed significantly higher infiltration rates than the ZT plots.…”
Section: Infiltration Rate (Ir)mentioning
confidence: 99%